2005
DOI: 10.1590/s0100-40422005000300005
|View full text |Cite
|
Sign up to set email alerts
|

Evidências da formação de monocamada de óxido de alumínio sobre sílica, através de reações de enxerto

Abstract: REACTIONS. Aluminum oxide was dispersed on a commercial silica gel surface, using successive grafting reactions. The reaction products were characterized by N 2 adsorption-desorption isotherms, scanning electron microscopy and infrared spectroscopy. The progressive incorporation of aluminum, up to 5.5% (w/w), does not produce agglomeration of alumina, since changes in the original pore size distribution of the silica matrix were not observed. The aluminum oxide covers homogeneously the silica surface.Keywords:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
0
7
0
2
Order By: Relevance
“…The found BET surface area values of the adsorbents were similar to that obtained for pure silica, and from the pore size distribution curves, a very similar pore dimension was clearly observed. The maintenance of the primary particle size, surface area values, and pore size distributions of the adsorbents similar to the pure silica ones is evidence that the organic groups were immobilized on the silica surface, forming a monolayer [36], without formation of agglomerates that could result in pore blocking or enlargement of particles.…”
Section: Synthesis and Characterization Of Aah Si And Aad Simentioning
confidence: 84%
“…The found BET surface area values of the adsorbents were similar to that obtained for pure silica, and from the pore size distribution curves, a very similar pore dimension was clearly observed. The maintenance of the primary particle size, surface area values, and pore size distributions of the adsorbents similar to the pure silica ones is evidence that the organic groups were immobilized on the silica surface, forming a monolayer [36], without formation of agglomerates that could result in pore blocking or enlargement of particles.…”
Section: Synthesis and Characterization Of Aah Si And Aad Simentioning
confidence: 84%
“…For this study, the zinc standard solutions were buffered with different types of buffers, whose concentrations were maintained at 0.05 mol L (Si-O-Al-O-H and Si-O-Nb-O-H). 41,42 As a consequence, the adsorption is very low at low pH values owing to the protonation of the oxygen centers. On the other hand, higher adsorption of Zn 2+ is observed in alkaline medium.…”
Section: Optimization Of Adsorbent Preconcentration Systemmentioning
confidence: 99%
“…Silica is an important support to active phases in catalysis due to its considerable porosity and structural rigidity. Studies have revealed the possible contribution to stabilization and prevention of sintering active phases, which are scattered on its surface (Cónsul et al 2005). SEM micrographs of the CuO/SiO 2 photocatalyst (b) showed impregnation of CuO on the silica surface, as well as discontinuity and rough surface, whereas the pure silica surface (a) was homogeneous.…”
Section: Photocatalyst Characterizationmentioning
confidence: 99%